Current knowledge and breeding strategies for management of aphid-transmitted viruses of pepper (Capsicum spp.) in Africa - Zohoungbogbo, Herbaud P. F.; Vihou, Fabrice; Achigan-Dako, Enoch G.; Barchenger, Derek W. (Frontiers in Plant Science, 2024)
Aphid-transmitted viruses cause significant losses in pepper production worldwide, negatively affecting the yield and quality. The emergence of new aphid-transmitted viruses or development of variants as well as the occurrence in mixed infections make management a challenge. Here, we overview the current status of the distribution, incidence and phylogeny of aphids and the viruses they transmit in pepper in Africa; outline the available genetic resources, including sources of resistance, resistance genes and molecular markers; and discuss the recent advances in understanding the genetic basis of resistance to the predominant African viruses infecting pepper. Pepper veinal mottle virus (PVMV; Potyvirus); Potato virus Y (PVY; Potyvirus), Chili veinal mottle virus (ChiVMV; Potyvirus), Cucumber mosaic virus (CMV; Cucumovirus) and Pepper veins yellow virus (PeVYV; Polerovirus) have been reported to be the most widespread and devastating aphidtransmitted viruses infecting pepper across Africa. Co-infection or mixed infection between aphidtransmitted viruses has been detected and the interrelationship between viruses that co-infect chili peppers is poorly understood. Establishing and evaluating existing and new diversity sets with more genetic diversity is an important component of developing host resistance and implementing integrated management strategies. However, more work needs to be done to characterize the aphidtransmitted viral strains across Africa and understand their phylogeny in order to develop more durable host resistance. In addition, a limited number of QTLs associated with resistance to the aphid-transmitted virus have been reported and QTL data are only available for PVY, ChiVMV and CMV mainly against European and Asian strains, although PVMV is likely the most important aphid-transmitted viral disease in Africa. There is a need to identify germplasm resources with resistance against various aphid-transmitted virus strains, and subsequent pyramiding of the resistance using marker-assisted selection could be an effective strategy. The recent advances in understanding the genetic basis of the resistance to the virus and the new breeding techniques that can be leveraged to accelerate breeding for aphid-transmitted virus in pepper are proposed as strategies to more efficiently develop resistant cultivars. The deployment of multi-genetic resistances in pepper is an effective and desirable method of managing viral-diseases in Africa in a sustainable manner.